PEREBUTAN “OTORITAS” DALAM HUKUM ISLAM - Budi Juliandi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
This study will examine whether the use of authority held by variants of ulama institutions in Aceh Tamiang such as MPU (the Consultative Assembly of Ulamas), Dayah (traditional Islamic schools), and Muhammadiyah is running properly. There is a recognition that one institution had more authoritative than another. This recognition raises the attitudes of authoritarianism and intolerance because of the claims as the owner of a single authority. The rejection toward such this authority implied a rejection of any legal form issued by an institution of ulamas, both in the form of a fatwa, or taushiyah. Although MPU Aceh Tamiang gained the authority in Islamic law from the local government, but it does not mean that other clerical institutions do not have the authority as such. MPU Aceh Tamiang put themselves as a counterweight to the power of clerical conservatism represented by Dayah (traditional Islamic schools) in Aceh, and moderate strength that carried by mustafawiyin (the alumni of Mustafawiyah Islamic boarding school in North Sumatra), a group of Muslim scholars (the alumni of Islamic higher education), and or the alumni of non- traditional Islamic schools. This study questioned Hilmi’s opinion (2008) who said that religious institutions sponsored by the government (such as MPU) become entry critical points of intolerant attitudes towards the diversity in religious beliefs.